Effects of n-3 Polyunsaturated Fatty Acid Supplementation on Cardiovascular Indices in Type 2 Diabetes: A Meta-analysis of Randomized Controlled Trials - Ruiyao Li; Yao Wang; Jing Xu; Jiahao Yu; Bin Li (Reviews in Cardiovascular Medicine)
Background: Individuals with type 2 diabetes (T2DM) face a significantly increased risk of cardiovascular disease. This study aims to explore the impact of omega-3 polyunsaturated fatty acids (n-3 PUFAs) on cardiovascular indices in this population. Although the benefits of n-3 PUFAs on cardiovascular health and glycemic outcomes are highly regarded, previous research reports have shown inconsistent results. Therefore, a comprehensive meta-analysis is needed to gain a deeper understanding of the specific effects of n-3 PUFAs on patients with T2DM. To examine the effect of n-3 PUFAs on cardiovascular indices in T2DM using a meta-analysis of randomized controlled trials (RCTs). Methods: Online databases including PUBMED, EMBASE and Cochrane libraries were searched up to December 2023. We assessed the overall weighted mean difference in cardiovascular indices between the group supplemented with n-3 PUFAs and the control group. The differences were compared uniformly using pre- and post-treatment differences. Results: Supplementation with n-3PUFAs in patients diagnosed solely with T2DM significantly reduced low density lipoprotein (LDL) (weighted mean difference (WMD) = –3.92, 95% confidence interval (CI) = –6.52 to –1.32, p = 0.003 < 0.05), triglycerides (WMD = –23.94, 95% CI = –34.95 to –12.93, p = 0.000 < 0.05), cholesterol (WMD = –8.39, 95% CI = –12.06 to –4.72, p = 0.000 < 0.05), glycated hemoglobin (WMD = –0.25, 95% CI = –0.41 to –0.06, p = 0.003 < 0.05) and the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) index (WMD = –0.55, 95% CI = –0.81 to –0.29, p = 0.000 < 0.05). All other differences in lipid indices, glycemic indices, inflammatory parameters and blood pressure were not statistically significant (p > 0.05). Supplementation with n-3 PUFAs decreased high density lipoprotein (HDL) concentration in patients with T2DM and coronary heart disease (CHD) (WMD = –3.92, 95% CI = –6.36 to –1.48, p = 0.002 < 0.05). There were no significant differences in LDL, triglycerides, cholesterol, and C-reactive protein (CRP) in patients with T2DM and CHD (p > 0.05). Conclusions: N-3 PUFAs improved lipid levels and long-term blood glucose levels in patients diagnosed solely with T2DM, but did not significantly improve blood pressure inflammatory markers. N-3 PUFAs showed no significant improvement in blood lipid and inflammatory indexes in patients with T2DM and CHD. The PROSPERO registration: CRD42024522262, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024522262.